2023
DOI: 10.3390/en16145566
|View full text |Cite
|
Sign up to set email alerts
|

Convex Stochastic Approaches for the Optimal Allocation of Distributed Energy Resources in AC Distribution Networks with Measurements Fitted to a Continuous Probability Distribution Function

Abstract: This paper addresses the optimal stochastic allocation of distributed energy resources in distribution networks. Typically, uncertain problems are analyzed in multistage formulations, including case generation routines, resulting in computationally exhaustive programs. In this article, two probabilistic approaches are proposed–range probability optimization (RPO) and value probability optimization (VPO)–resulting in a single-stage, convex, stochastic optimal power flow problem. RPO maximizes probabilities with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The findings demonstrated that the strategy that was presented is flexible and has high performance. A greedy randomized adaptive search procedure (GRASP) with Tabu search was used to optimize the allocation and dimension of DGs in order to minimize the overall losses in the power distribution feeders [22,23].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The findings demonstrated that the strategy that was presented is flexible and has high performance. A greedy randomized adaptive search procedure (GRASP) with Tabu search was used to optimize the allocation and dimension of DGs in order to minimize the overall losses in the power distribution feeders [22,23].…”
Section: Literature Reviewmentioning
confidence: 99%